THIRTY.THREE NEW RECORD DICOT SPECIES FOR BAGHDAD CITY AND FOUR NEW RECORDS TO IRAQI FLORA AT IRAQ - A., Lobab G.; Al.Musawi, Ali H. A. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
This study deals with the species were recorded for the first time in Baghdad City discovered about thirty.three species distributed throughout many regions belong to fourteen families, which were Aizoaceae, Amaranthaceae, Asteraceae, Boraginaceae, Brassicaceae, Caryophyllaceae, Euphorbiaceae, Fabaceae, Papaveraceae, Plantaginaceae, Polygonaceae, Rosaceae, Zygophyllaceae. According to the results of the current study showed that about 34 species were recorded for the first time grown throughout Baghdad and its surrounding areas including Al.Zafaraniya region, Al.Rashidiya region, Aqraquf region, Abu.Nuass gardens and parks, Zyaona and Al.Jadiriyah gardens, Al.Radwanea orchards, Basmaia campus, Abu.Ghraib region, and Al.Zoraa gardens. recoding four of them as new record for Iraq, which were Amsinckia menziesii (Lehn.) A. Nelson & J.F. Macbr. (Boraginaceae), Carduus tenuiflours Curtis (Asteraceae), Medicago polymorpha var. spotii Al.Azerj &Al.Musawi, and Trifolium repens var. spotii Al.Azerj &Al.Musawi (Fabaceae).